The Influence of Maturity Offset, Strength, and Movement Competency on Motor Skill Performance in Adolescent Males - Andrew W. Pichardo; Jon L. Oliver; Craig B. Harrison; Peter S. Maulder; Rhodri S. Lloyd; Rohan Kandoi (MDPI AG, 2019)
This study aimed to examine the extent to which maturity offset, strength, and movement competency influences motor skill performance in adolescent boys. One hundred and eight secondary school boys completed anthropometric and physical testing on two non-consecutive days for the following variables: Maturity offset, isometric mid-thigh pull absolute (IMTPABS) and relative (IMTPREL) peak force, resistance training skills quotient, 10-, 20-, and 30-m sprint time, countermovement jump height, horizontal jump distance, anaerobic endurance performance, and seated medicine ball throw (SMBT). The IMTPREL displayed significant small to large correlations with all performance variables (r = 0.27−0.61), whereas maturity offset was significantly correlated with IMTPABS (r = 0.69), sprint (r = 0.29−0.33), jump (r = 0.23−0.34), and SMBT (r = 0.32). Absolute and relative strength were the strongest predictors of all performance variables and combined with maturity to explain 21%−76% of the variance. Low and average relative strength boys were nearly eight times (odds ratio: 7.80, confidence interval: 1.48−41.12, p < 0.05) and nearly four times (odds ratio: 3.86, confidence interval: 0.95−15.59, p < 0.05) more likely to be classified as lower competency compared to high relative strength boys. Relative strength has more influence on motor skill performance than maturity when compared with movement competency.